Embryonal Rhabdomyosarcoma of the Biliary Tree as a Differential in a Paediatric Patient Presenting with Biliary Dilatation: Not Always a Choledochal Cyst - Tripathy, Tara Prasad; Patidar, Yashwant; Chandel, Karamvir; Varadarajan, Annapoorani; Sood, Vikrant; Thapar Laroia, Shalini (Acta medica Lituanica, 2022)
Rhabdomyosarcoma is a soft tissue malignant musculoskeletal tumour and is the most prevalent soft-tissue sarcoma in the paediatric population. Although, Embryonal RMS of the biliary tree is a rare entity, however, it is the most common cause of paediatric malignant obstructive jaundice. We present a 4-year-old child who had symptoms of obstructive jaundice and palpable liver. The non-contrast magnetic resonance imaging and magnetic resonance cholangiopancreatography (MRCP) features were consistent with choledochal cyst. However, contrast enhanced computed tomography and PET CT images revealed biliary RMS as the differential diagnosis. Percutaneous biopsy followed by histopathology confirmed the diagnosis of embryonal biliary RMS. Since embryonal rhabdomyosarcoma is uncommonly recorded in the literature and can mimic the appearance of a choledochal cyst, this case report emphasises the necessity of keeping embryonal RMS as a differential in paediatric cases of obstructive jaundice.
Keywords: biliary rhabdomyosarcoma; choledochal cyst; diffusion weighted imaging